Experimental and theoretical inquiry into optical properties of graphene derivatives. (9th October 2020) - Valimukhametova, Alina; Ryan, Conor; Paz, Thomas; Grote, Fabian; Naumov, Anton V
Abstract: Graphene oxide (GO), a functional derivative of graphene, is a promising nanomaterial for a variety of optoelectronic applications as it exhibits fluorescence and maintains many of graphene's beneficial physical properties. although other graphene derivatives are chemically plausible and may serve to the benefit of the aforementioned applications, GO remains the one heavily used. the nature of optical behavior of other graphene derivatives has yet to be fully understood and studied. in this work we develop a variety of graphene derivatives and characterize their optical properties concomitantly suggesting a unified model for optical emission in graphene derivatives. in this process we examine the influence of different functional groups on the surface of graphene on its optoelectronic properties. mildly oxidized graphene (oxo-g1 ), nitrated graphene, arylated graphene, brominated graphene, and fluorinated graphene are obtained and characterized via TEM and EDX, FTIR and fluorescence spectroscopies with the latter indicating a potential band gap-derived fluorescence from each of the materials. this suggests that optical properties of graphene derivatives have minimal functional group dependence and are manifested by the localized environments within the flakes. this is confirmed by the hyperchem theoretical modeling of all aforementioned graphene derivatives indicating a similar electronic configuration for all, assessed by the pm3 semi-empirical approach. this work can further serve to describe and predict optical properties of similar graphene-based structures and promote graphene derivatives other than GO for utilization in research and industry.